1976
DOI: 10.2307/1936194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varying Oxygen Concentrations on the Filtering Rate of Daphnia Pulex

Abstract: Knowledge of factors affecting feeding efficiency is of vital importance to understanding any organism's relationship to its environment. The present study reports on the effect of one factor–variation in O_2 concentration–on the filtering rate of a common freshwater zooplankton species, Daphnia pulex. Measurements of D. pulex filtering rate were made under exposure to a wide range of O_2 concentrations and over periods of time ranging from < 1 h to 15 days. Oxygen was found to have a significant effect on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 27 publications
0
32
1
Order By: Relevance
“…However, it has been demonstrated that low oxygen reduces the filtration rate of zooplankton. Kring and O'Brien (1976) found that the filtration rate of the freshwater cladoceran, Daphnia pulex, decreased sharply when oxygen concentrations fell below 3 mg liter-I. This reduction in filtration activity may be a response to reduce metabolic rate in low-oxygen conditions.…”
Section: Resultsmentioning
confidence: 88%
“…However, it has been demonstrated that low oxygen reduces the filtration rate of zooplankton. Kring and O'Brien (1976) found that the filtration rate of the freshwater cladoceran, Daphnia pulex, decreased sharply when oxygen concentrations fell below 3 mg liter-I. This reduction in filtration activity may be a response to reduce metabolic rate in low-oxygen conditions.…”
Section: Resultsmentioning
confidence: 88%
“…This might explain why the critical ambient oxygen concentration of 3.9·mg·O2·l -1 (PO 2crit =7.9·kPa), which was predicted for the fasting state with doubled perfusion rate (Fig.·7A), was higher than the critical oxygen concentrations of 1.3-3.0·mg·O2 l -1 reported for filtering and respiration rates of Hb-poor D. magna and D. pulex (Kring and O'Brien, 1976; Oxyregulatory mechanisms in Daphnia magna Heisey and Porter, 1977;Kobayashi and Hoshi, 1984). The high sensitivity of the model to changes in the solubility coefficient for oxygen in the haemolymph (αH) indicates that Hb can have a pronounced effect on PO 2crit , since it enhances both the convective and diffusive transport of oxygen in the haemolymph.…”
Section: Discussionmentioning
confidence: 85%
“…8). Daphnia in water with oxygen levels greater than 5 mg L Ϫ1 (i.e., the trout zone) were more vulnerable to predation, whereas those at depths with oxygen concentrations below 3 mg L Ϫ1 were presumably subject to elevated physiological stress (Kring and O'Brien 1976). Oxygen concentrations below 1 mg L Ϫ1 appeared to set the lower limit of the population's spatial distribution later in the year (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Depths with oxygen concentrations between 3 and 5 mg L Ϫ1 are defined as the ''refuge zone,'' because oxygen levels are lower than the threshold for trout but greater than the threshold concentration at which Daphnia become physiologically stressed. Kring and O'Brien (1976) showed that D. pulex (a closely related species) had significantly higher filtering rates and elevated hemoglobin production at oxygen concentrations below 3 mg L Ϫ1 . Depths with oxygen concentrations between 1 and 3 mg L Ϫ1 are defined as the ''hypoxic zone.''…”
Section: Methodsmentioning
confidence: 99%